Design of metamaterial loaded microstrip patch antenna array - Usha, Tamanna Yeasmin; Choudhury, Tarannum; Anushka, Hanan Ashrafi (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.